1997
DOI: 10.1177/089033449701300309
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Feeding Glucose Water to Breastfeeding Newborns on Weight, Body Temperature, Blood Glucose, and Breastfeeding Duration

Abstract: In order to determine the effect of feeding glucose water on breastfeeding newborns, we randomly distributed 180 normal newborns into two groups: a glucose water group (GW), fed 5% glucose solution during the first 3 days of life in addition to being breastfed; and an exclusively breastfed nonglucose water group (NGW). The following data were evaluated: weight at 6, 12, 24, 48, and 72 hours of life; temperature during the first 72 hours of life; serum glucose level at 6, 12, 24, and 48 hours; total duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 6 publications
1
51
0
5
Order By: Relevance
“…23 In the maternity ward, 32.4% of participating infants received formula (8.9% were nonbreastfeeding and 23.5% were complementary fed). The present secondary data analysis included the subsample of infants (n = 1656; 67.6%) who were exclusively or predominantly breastfed in the maternity ward.…”
Section: Methodsmentioning
confidence: 99%
“…23 In the maternity ward, 32.4% of participating infants received formula (8.9% were nonbreastfeeding and 23.5% were complementary fed). The present secondary data analysis included the subsample of infants (n = 1656; 67.6%) who were exclusively or predominantly breastfed in the maternity ward.…”
Section: Methodsmentioning
confidence: 99%
“…Martin-Calama et al (42) found in a randomized trial that routine supplementation with dextrose water reduced the likelihood of hypoglycemia. Randomized clinical trials in SGA (43) and appropriate-for-gestationalage (44) infants found that augmented glucose formulas raise blood glucose and prevent hypoglycemia (Level 1b).…”
Section: Asymptomatic Hypoglycemiamentioning
confidence: 99%
“…However, supplementation with water or sugar water has been studied less than formula supplementation (19,20,22) . Knowledge about the possible influence of other health service-related factors is limited.…”
mentioning
confidence: 99%